Control interno de las cuentas por pagar a proveedores de la Empresa Dismero S.A. de la ciudad de Babahoyo en el periodo 2023. - Rodríguez Pérez, Edison Denis (2024)
Accounts payable to suppliers represent the amount of money that a company owes to its suppliers for the acquisition of merchandise and goods, which are current payments since they must be settled within a minimum period of one year. These accounts payable are part of the fundamental and very important in business economic activity. This case study shows the importance of carrying out internal control of accounts payable and correct percentage analysis of indebtedness by applying vertical analysis to the financial statements. Therefore, the objective of this case study was to analyze the behavior of accounts payable to suppliers using an internal control questionnaire. The methodological framework consisted of a descriptive study to describe and understand the information collected in the interview with the accountant. , likewise, it was based on inductive and deductive methods to understand the study problem. The results of this investigation allow us to conclude that accounts payable are of vital importance in the balance of the Dismero company. Likewise, the weaknesses found were the inadequate process in the payment period to suppliers, which causes unstable commercial relations and poor performance. credit reputation, as well as interest payments that would affect the pocket of our company.